2009
DOI: 10.1021/jf902560x
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Joker among the Maize Endogenous Reference Genes for Genetically Modified Organism (GMO) Detection

Abstract: The comparison of five real-time polymerase chain reaction (PCR) methods targeted at maize ( Zea mays ) endogenous sequences is reported. PCR targets were the alcohol dehydrogenase (adh) gene for three methods and high-mobility group (hmg) gene for the other two. The five real-time PCR methods have been checked under repeatability conditions at several dilution levels on both pooled DNA template from several genetically modified (GM) maize certified reference materials (CRMs) and single CRM DNA extracts. Slope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…These results indicate that the presence of a single target site for hmg and ZmAdh1 and of two targets for aldolase is not limited to only one reference material, but is confirmed for both CRMs used in the study. Both the assay for hmg and for ZmAdh1 could be used in GMO quantification, although one particular reaction mix recipe for hmg was reported to be more stable in terms of quantification performance according to Paternò et al (2009) . The assay for aldolase instead targets two sequences that amplify with different efficiencies due to the presence of mismatches in the reverse primer and in the probe ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the presence of a single target site for hmg and ZmAdh1 and of two targets for aldolase is not limited to only one reference material, but is confirmed for both CRMs used in the study. Both the assay for hmg and for ZmAdh1 could be used in GMO quantification, although one particular reaction mix recipe for hmg was reported to be more stable in terms of quantification performance according to Paternò et al (2009) . The assay for aldolase instead targets two sequences that amplify with different efficiencies due to the presence of mismatches in the reverse primer and in the probe ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A similar situation also exists for other crop species [25], such as maize, rapeseed and cotton. The maize and rapeseed-specific reference gene detection systems have been systematically compared and validated [15][16][17]. The results of these studies revealed that the comparison and validation of such reference genes is essential to standardize GM detection and to obtain comparable results between different assays.…”
Section: Discussionmentioning
confidence: 99%
“…The use of various endogenous reference genes in rice detection systems could cause confusion similar to that which has occurred with maize and rapeseed [14][15][16][17]. One study has investigated the amplicon SNPs of some rice genes [18], but the mutual commutability among these genes and the advantages and flaws of each gene for the quantitative detection of GM rice have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the choice, as already stated in a previous study (Paternò et al 2009), from both a theoretical and technical point of view, there is no reason for changing the PCR reference system according to the GM event to be quantified (except for very peculiar situations related to food matrix and amplicon length). Therefore, the use of a single taxon-specific PCR reference system for enforcement purposes is not only advisable for practical reasons but also sensible from a scientific perspective.…”
Section: Precision-relative Repeatability Standard Deviationmentioning
confidence: 99%